Replacement analysis of amine circulation pumps - Abd Majid, M.A. (Asian Research Publishing Network, 2016)
The paper highlight the study on replacement analysis of amine circulation pumps installed at a gas processing complex. The pumps were commissioned in 1998. Analysis on operation and maintenance costs as well as price of noncompliance (PONC) during the last three years indicated increasing trends for both costs. Since the pumps are more than sixteen years old the increasing trends of both costs are expected. It is then appropriate to consider a replacement for the pumps. The study on replacement was undertaken. Marginal cost (MC) and equivalent uniform annual cost (EUAC) were used to analyse the old pumps (defenders) and the new pumps (challengers) respectively. The MC of the defenders was then compared with the EUAC of the challengers. Results from the analysis indicate the MC of defenders are very much higher than EUAC of the challengers even for the year 2015. Thus it is recommended the defenders to be replaced with the challengers. Sensitivity analysis on the challengers indicates that the energy cost has the greatest influence on the present worth of the challengers. Â© 2006-2016 Asian Research Publishing Network (ARPN).